Intestinal Autophagy Improves Healthspan and Longevity in C. elegans during Dietary Restriction - Gelino, Sara (PLoS Genet, 2016)
Dietary restriction (DR) is a dietary regimen that extends lifespan in many organisms. One mechanism contributing to the conserved effect of DR on longevity is the cellular recycling process autophagy, which is induced in response to nutrient scarcity and increases sequestration of cytosolic material into double-membrane autophagosomes for degradation in the lysosome. Although autophagy plays a direct role in DR-mediated lifespan extension in the nematode Caenorhabditis elegans, the contribution of autophagy in individual tissues remains unclear. In this study, we show a critical role for autophagy in the intestine, a major metabolic tissue, to ensure lifespan extension of dietary-restricted eat-2 mutants. The intestine of eat-2 mutants has an enlarged lysosomal compartment and flux assays indicate increased turnover of autophagosomes, consistent with an induction of autophagy in this tissue. This increase in intestinal autophagy may underlie the improved intestinal integrity we observe in eat-2 mutants, since whole-body and intestinal-specific inhibition of autophagy in eat-2 mutants greatly impairs the intestinal barrier function. Interestingly, intestinal-specific inhibition of autophagy in eat-2 mutants leads to a decrease in motility with age, alluding to a potential cell non-autonomous role for autophagy in the intestine. Collectively, these results highlight important functions for autophagy in the intestine of dietary-restricted C. elegans.